2018
DOI: 10.1002/dc.24041
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p63 immunostaining in liquid‐based cytology (BD SurePath) of breast fine‐needle aspiration

Abstract: The diagnostic accuracy of breast FNAC was significantly improved by adding LBC-p63 immunostaining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In these circumstances, IHC may have to be performed on cytology smear slides. Many studies have demonstrated that successful IHC staining can be achieved on a variety of cytology specimens including direct smears, 18–20 ThinPrep, 21,22 SurePath, 23,24 cytospin, 25 and slides prepared by cell transfer technique 26,27 . (Table 1) The only exception is Diff Quik stained slides, which are not suitable for IHC staining 26,27 …”
Section: Performing Ihc On Cytology Smears When An Adequate Cb Is Not...mentioning
confidence: 99%
See 1 more Smart Citation
“…In these circumstances, IHC may have to be performed on cytology smear slides. Many studies have demonstrated that successful IHC staining can be achieved on a variety of cytology specimens including direct smears, 18–20 ThinPrep, 21,22 SurePath, 23,24 cytospin, 25 and slides prepared by cell transfer technique 26,27 . (Table 1) The only exception is Diff Quik stained slides, which are not suitable for IHC staining 26,27 …”
Section: Performing Ihc On Cytology Smears When An Adequate Cb Is Not...mentioning
confidence: 99%
“…All IHC need validation because of the use of methanol-based fixative, which may interfere IHC. Expensive equipment on a variety of cytology specimens including direct smears, [18][19][20] ThinPrep, 21,22 SurePath, 23,24 cytospin, 25 and slides prepared by cell transfer technique. 26,27 (Table 1) The only exception is Diff Quik stained slides, which are not suitable for IHC staining.…”
Section: Self-clottingmentioning
confidence: 99%